Lead poisoning in children and neurological symptoms (Research, Society and Development, 2022)
Introduction: Lead poisoning in children is a recurring public health problem in several parts of the world, leading to numerous neurological problems in children. Objective: To compile findings from studies that describe neurological symptoms in children exposed to this metal, thus providing a basis for researchers and public policy makers with the intention of guiding future actions on the subject. Methods: A narrative review of the literature was carried out with a systematic search for articles on the subject, from January 2007 to March 2022, in the SciELO, MedLine, LILACS and PsycInfo databases. Results: It was possible to observe the relationship between lead poisoning in children and the presence of neurological symptoms, with effects identified in the blood concentration from 2µg/dL to the highest concentration of 706µg/dL. Conclusion: Lead poisoning in children is a worrying reality due to the seriousness of its sequelae. Children who live near facilities that use lead as a raw material have greater exposure, may become intoxicated and develop more severe symptoms. In view of the analyzed studies, there is a lack of research that appreciates the Brazilian socio-environmental reality; for that, it is necessary to encourage trials that address this situation.